Inter-Institutional Cooperation and Migrants' Financial Education: An Italian Case Study - Samuel Nocito; Alessandra Venturini (Institute of Labor Economics (IZA), 2024)
This study evaluates the effect of a financial education program on migrants, emphasizing the importance of inter-institutional cooperation. The Italian case study, the "Welcome-ED" project—a partnership between the Municipality of Turin and the Turin Museum of Savings (MoS)—aimed to provide tailored financial education to diverse migrant groups, relying on cooperation with various local migration center entities: cooperatives, non-profit associations, and provincial centers for adult education. Our evaluation reveals a significant positive increase in migrants' financial literacy after participating in the project. Furthermore, when we redefine the MoS evaluation criteria employing a model from Item Response Theory (IRT), we document that the post-course migrants' greatest improvement was in the topic identified as most difficult by the IRT model. The study documents variations in the project's results, with migrants from cooperatives and non-profit associations benefiting more than those from provincial centers for adult education, primarily due to the different compositions of the migrant groups served. Our findings also highlight the significance of financial education for African migrants, a substantial part of migrants in Europe. The program evaluation underscores the essential role of cooperation between public and private institutions, cooperatives, and non-profit associations in expanding the reach and effectiveness of financial education projects for migrants. We finally emphasize the strengths and limitations of the program, providing recommendations for future enhancement of similar initiatives.
Keywords: D14; L30; J15; P13; 330; migrants; institutions; cooperatives; non-profit; financial literacy